2014
DOI: 10.1016/j.amjmed.2013.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Free-roaming Kissing Bugs, Vectors of Chagas Disease, Feed Often on Humans in the Southwest

Abstract: BACKGROUND Kissing bugs, vectors of Trypanosoma cruzi, the parasite that causes Chagas disease, are common in the desert Southwest. After a dispersal flight in summer, adult kissing bugs occasionally gain access to houses where they remain feeding on humans and pets. How often wild, free-roaming kissing bugs feed on humans outside their homes has not been studied. This is important because contact of kissing bugs with humans is one means of gauging the risk for acquisition of Chagas disease. METHODS We captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 20 publications
3
41
0
3
Order By: Relevance
“…Results of our study, as well as those of Stevens et al ( 10 ) and Kjos et al ( 14 ), reject the assertion that kissing bugs in North America prefer blood from wild animals, which has been one explanation for the low prevalence of Chagas disease in the United States. Our study provides evidence of frequent vector/human/ T. cruzi contact in Louisiana and reveals the potential for transmission in the United States.…”
Section: Discussionsupporting
confidence: 78%
“…Results of our study, as well as those of Stevens et al ( 10 ) and Kjos et al ( 14 ), reject the assertion that kissing bugs in North America prefer blood from wild animals, which has been one explanation for the low prevalence of Chagas disease in the United States. Our study provides evidence of frequent vector/human/ T. cruzi contact in Louisiana and reveals the potential for transmission in the United States.…”
Section: Discussionsupporting
confidence: 78%
“…2 Kissing bug domiciliation or infestation of human dwellings has been described in this region of southern Arizona. 5,6 Furthermore, T. rubida in Tucson often harbor T. cruzi: 128 T. rubida captured in a zoological park had a rate of carriage of T. cruzi of 25%. 7 An earlier study by Reisenman et al 8 demonstrated a rate of carriage of T. cruzi by T. rubida to be 41% (N = 158 bugs).…”
Section: Discussionmentioning
confidence: 99%
“…With regards to epidemiological importance, Triatoma gerstaeckeri , Triatoma sanguisuga , and Triatoma lecticularia have been implicated as the vectors of autochthonous transmission in the United States [2327]; and all three species are found in close association with homes in rural areas of Texas and Louisiana [2831]. Human blood meals are common in Triatoma rubida from Arizona and California [22,32]. Many species within the Lecticularia complex show morphological variation across their broad geographic range including T. rubida and T. sanguisuga .…”
Section: Introductionmentioning
confidence: 99%